Child-headed households because of the trauma surrounding HIV/AIDS - Maqoko, Zamani (HTS teologiese studies, 2007)
By the year 2002 14 million children had been orphaned globally because of the HIV/AIDS pandemic. A great number of these have become the heads of households, are forced to look after themselves and siblings, drop out of school, are vulnerable to many forms of abuse and have found work to take care of themselves and their siblings. Misinformation, ignorance and prejudice concerning HIV/AIDS limit the willingness of a community to provide for the orphans who have been affected by the disease. This article aims to address the question why this is also the case in South Africa and why the African philosophy of “ubuntu” (humaneness), does not seem to make a difference. This study build upon fieldwork undertaken in the Bophelong area among HIV/AIDS orphans who function as heads of households and children who have been orphaned due to circumstances other than HIV/AIDS. The article concludes that religious communities can fill the gap left by the lack of “ubuntu” and can play a major role in nurturing HIV/AIDS orphans who function as heads of households. Churches can build a supportive environment where HIV/AIDS orphans and other vulnerable children can feel accepted.